Radio-tracing techniques applied in a marine ecosystem, the case of a submarine groundwater source at southern Peloponnesus - Patiris, D. L.; Eleftheriou, G.; Karageorgis, A. P.; Georgopoulos, D.; Papadopoulos, V.; Stamoulis, K.; Ioannides, K. G.; Vlastou, R.; Tsabaris, C. (HNPS Advances in Nuclear Physics, 2019)
The submarine discharge of groundwater (SGD) into the coastal zone has been recognized as an important component of the hydrological cycle. Quantities of groundwater flowing toward coastal aquifers are leaded under the seafloor and due to geomorphologic causes may discharge into the coastal zone. At some locations the quantity of the water is large enough to establish these springs as valuable water sources. The estimation of the submarine groundwater flux is complicated by conventional methods. Instead, measurements of a variety of radioisotopes (222Rn, 214Pb, 226Ra, 228Ra, 40K, 3H) as tracers provide a means to obtain integrated flux estimations as well as residence time, the age of the water and a factor of ground-sea water mixing process. Results from the current study at Stoupa’s (S. Peloponnesus) SGD source are presented revealing the importance of radio-tracing methods to the investigation of marine ecosystems.